Co-MOF@MXene hybrids flame retardants for enhancing the fire safety of thermoplastic polyurethanes. (October 2022) - Shi, Congling; Wan, Mei; Hou, Zhengbo; Qian, Xiaodong; Che, Honglei; Qin, Yueping; Jing, Jingyun; Li, Jian; Ren, Fei; Yu, Bin; Hong, Ningning
Highlights: MOFs was assembled with two-dimensional MXene nanosheets to form a novel flame retardant hybrids (Co-MOF@MXene) by solvothermal method. The mechanism of Co-MOF@MXene hybrids is based on the interaction of end-group motifs on MXene and the unsaturated sites of metal ions on MOF. TPU/Co-MOF@MXene composites showed excellent fire safety properties. The excellent fire safety properties of TPU/Co-MOF@MXene composites are due to the physical barrier, catalytical carbonization, and gas-phase flame retardant of Co-MOF@MXene hybrids. Abstract: Thermoplastic polyurethane (TPU) is the most used polyurethane, but its highly flammable characteristic restricts its extensive use. In this work, Co-MOF@MXene hybrids flame retardants were synthesized and incorporated into TPU. The flame-retardant characteristics of TPU composites were investigated by cone calorimeter test and thermogravimetric analyzer. Compared with TPU, the peak heat release rate and total heat release rate of TPU/Co-MOF@MXene composites were reduced by 28.3% and 14.5%, respectively; and the smoke production rate and total smoke production of the composites with only 2 wt% Co-MOF@MXene hybrids were also reduced by 58.8% and 47.5%, respectively. Furthermore, the char residues of TPU/Co-MOF@MXene composites were about 2 times that of pure TPU. Systematical characterizations were then carried out to investigate the flame retardant mechanism of Co-MOF@MXene hybrids, highlighting the barrier effects of MXene combined with the catalytic effect of Ti and Co. The hybrids flame retardants greatly benefit the further development of TPU nanocomposites.